Optimizing Educational Scheduling: ACO-Based Lecture Schedule Preparation Application - Jhonlawi, Bonie Alkhan (International Enterprise Integration Association, 2024)
This research endeavors to revolutionize educational scheduling by introducing a Lecture Schedule Preparation Application founded on Ant Colony Optimization (ACO) algorithms. The study addresses the intricate challenges inherent in scheduling courses within educational institutions. By leveraging ACO's adaptability and optimization capabilities, the application aims to efficiently allocate courses to rooms, time slots, and days while considering diverse constraints, faculty preferences, and institutional requirements. The investigation delves into the application's design, implementation, and performance in comparison to traditional heuristic approaches and other metaheuristic algorithms. Emphasizing adaptability and user-centricity, the application incorporates user preferences and institutional constraints, aligning schedules more closely with real-world needs. Key findings highlight the application's efficacy in optimizing resource utilization, enhancing scheduling efficiency, and accommodating real-time changes. The study underlines the significance of ACO's scalability, adaptability, and robustness in handling complex scheduling scenarios prevalent in educational settings. The research contributes to the realm of educational scheduling by introducing an innovative and adaptable solution. The findings underscore the transformative potential of ACO algorithms in streamlining scheduling processes, thereby fostering a more harmonious and efficient educational environment.